2014
DOI: 10.1155/2014/597207
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Primary Malignant Tumor in a Patient with Possible Li-Fraumeni Syndrome: Synchronous Diagnosis of Postirradiation Sarcoma, Cutaneous Relapse of a Previous Soft Tissue Sarcoma, and Lung Adenocarcinoma

Abstract: We present a 46-year-old female patient who is diagnosed with synchronous postirradiation sarcoma, cutaneous relapse of a previous soft tissue sarcoma, and lung adenocarcinoma. More than one malignant tumor at the same time with an accompanying relapse of a previous malignant tumor is a rare entity. A relatively young patient diagnosed with adenocarcinoma of the urethra before age 40, which is an unusual tumor for that age, later three more different malignant tumors being diagnosed, two of which are synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the majority of cases, these tumors are metachronous and often related to radiotherapy administered to previous tumors [4,5]. Here we have presented the case of a young female patient with LFS who does not fit the typical description of these patients.…”
Section: Discussion/conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the majority of cases, these tumors are metachronous and often related to radiotherapy administered to previous tumors [4,5]. Here we have presented the case of a young female patient with LFS who does not fit the typical description of these patients.…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…In 1990, two independent studies reported that germline mutations in TP53, a tumor suppressor gene, were the primary factor involved in the development of LFS [2,3]. TP53 mutations have been associated with resistance to treatment in some case reports and these patients are more likely to develop radiation-induced secondary malignancies [4,5], which complicates disease management. The participation of a multidisciplinary team is crucial in determining the optimal course of treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%